Combination of Binary Integer Programming and Nonlinear Optimization for Artificial Lift Selection at Offshore X Field - Van Anggara, Denny
The decision of which artificial lift method to be used is very crucial to the long-term production of the field. Inaccurate selection can lead to reducing production and profit. Artificial Lift on offshore operation needs more concern because of the challenging area and hence higher operational cost. The aim of this study was to select the best artificial lift method on offshore site. The lift method here was constricted to electrical submersible pump and gas lift, which are fit for this area. The accurate selection of lift method on offshore site can maximize the oil production and profit. The study was conducted at “X” field which has low reservoir pressure. There were 6 producing wells to be evaluated. The rate of ESP was designed by optimizing the system liquid rates to get the maximum total oil production and utilizing Mixed Integer Programming. Then, gas-lift allocation was determined by solving the problem with the constraint of availability gas using nonlinear programming. The optimum gas injection rate was obtained. By applying binary integer programming, the objective function was optimized with the assigned decision binary variable and the oil production of each lift method as the input. The result showed that 5 of 6 wells were suitable for ESP than the gas lift. This happened because the optimization process was comparing the higher oil rates. Most of ESP methods showed significantly higher oil rates than the gas lift. The low reservoir pressure and high pressure drop along the tubing were the main factor. Nonetheless, binary integer programming was useful to tackle the selection problem. It can apply for many combinations of artificial lift method, wells, and additional constraints.